Perlindungan Hukum Terhadap Pekerja Kontrak Dalam Hubungan Kerja di Indonesia - I, Ismaidar; Bahirra, Aruf; Hutabarat, Samuel (Media Hukum Indonesia (MHI), 2025)
Legal protection for contract workers in Indonesia still faces various challenges despite being regulated under the Manpower Law and the Job Creation Law. In practice, there is suboptimal fulfillment of contract workers’ rights, such as fair wages, social security, and fair treatment in termination of employment. This study uses a literature review method to examine the regulations and their implementation within the context of industrial relations. The findings emphasize the important roles of the government, legislative, and judiciary in ensuring effective legal protection for contract workers. There is a need to enhance legal socialization, labor supervision, and policy adjustments that are responsive to realize justice and welfare in employment relationships in Indonesia.